First Oriental record of genus Neostroblia Heinrich (Hymenoptera, Ichneumonidae, Ctenopelmatinae) with description of one new species - Sheng, Mao-Ling; Watanabe, Kyohei; Huang, Rui-Fen (Zootaxa, 2022)
One new species, Neostroblia melana Sheng & Watanabe sp. nov., collected from Fanjingshan National Natural Reserve, Guizhou Province, China, is reported. A key to species of Neostroblia known in the world is provided. A key to similar genera of Mesoleiini is also provided.